Source studies of the history of Jadid schools - Imamov Ulug’bek Ismailovich (Global Scientific Publishing, 2023)
The cornerstone of the Jadid movement are the Jadid schools. This opinion is unanimously recognized by modern scientists. The original goal of this movement was to promote the identity of the nation, radically reform the sociopolitical system and the independence of the nation and homeland. It is known that only a new generation can make such big changes. To do this, it is necessary to educate a generation that keeps pace with developed countries. Traditional local schools, which brought up such great world thinkers as Farobi, Beruni, Ibn Sina, Ulugbek, Navoi, have been completely cut off from world development since the 16th century, moreover, local schools and education have fallen into decay due to the colonial system was not able to accomplish this great task with the help of the system. That is why the primary and main task of modern thinkers has become a radical reform of local schools, the creation of schools and higher educational institutions that meet the requirements of the time. Modern teachers have raised the issue of the revival of primary schools based on the “usuli savtiya” (“sound method”) method to the level of state policy: they created elementary alphabets, textbooks for individual subjects.
Keywords: Jadid; modern scientists; the independence of the nation; big changes